Pengaruh Strategi Bisnis dan Kinerja ESG terhadap Potensi Financial Distress pada Perusahaan di Negara-Negara ASEAN - Elvira Luthan; Muhammad Irfan; Asniati Bahari (Politeknik Ganesha Medan, 2025)
The objective of this study is to examine the impact of business strategy and ESG performance on the potential for financial distress among companies in ASEAN. The study population consists of all companies listed on ASEAN stock exchanges during the period 2016-2023. The sample data was collected using the purposive sampling technique and resulted in 1,977 sample data. The data used in this study was obtained from the Thomson Reuters database. The data were analyzed using the unbalanced panel data regression method using STATA software version 17. The results indicated that business strategy had no significant impact on the potential for companies to experience financial distress. Conversely, ESG performance had a positive and significant impact on the potential for companies to experience financial distress. Efforts to improve ESG performance have a major influence on company performance, because these efforts require large costs while support from stakeholders for ESG practices is still relatively small. Therefore, for the development of this study, it is suggested that future research can conduct research with a qualitative approach that explores the perspectives of various stakeholders regarding ESG practices implemented by the company. By involving the views and insights of these stakeholders, the research will have higher validity and accuracy, and provide a more comprehensive understanding.